Coarsening and dendritic instability of spheroidal graphite in high silicon cast iron under thermal cycling in the ferritic domain. (15th March 2020) - Ebel, André; Pegoraro, Mariana Alves; Malard, Benoit; Tenailleau, Christophe; Lacaze, Jacques
Abstract: High silicon ferritic spheroidal graphite cast irons have been developed for high temperature service, in particular under thermal cycling conditions. The theoretical maximum service temperature is defined as the upper limit of the two-phase ferrite+graphite domain, which increases with the alloy silicon content. While isothermal heat treatment close to this temperature showed little evolution of the graphite distribution, thermal cycling led to a significant coarsening of the graphite particles associated with dendritic overgrowth of the large graphite particles. This unexpected behaviour is here observed and described for the first time. Graphical abstract: Image, graphical abstract